2016
DOI: 10.1371/journal.pone.0147686
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obstructive Sleep Apnea on the Levels of Placental Growth Factor (PlGF) and Their Value for Predicting Short-Term Adverse Outcomes in Patients with Acute Coronary Syndrome

Abstract: BackgroundPlacental growth factor (PlGF) induces angiogenesis and promotes tissue repair, and plasma PlGF levels change markedly during acute myocardial infarction (AMI). Currently, the impact of obstructive sleep apnea (OSA) in patients with AMI is a subject of debate. Our objective was to evaluate the relationships between PlGF levels and both the severity of acute coronary syndrome (ACS) and short-term outcomes after ACS in patients with and without OSA.MethodsA total of 538 consecutive patients (312 OSA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Sun et al [32] reported that higher circulating ESM-1, previously named endothelial cell-specific molecule-1, correlated with the presence of CAD in patients with OSA. Furthermore, several studies demonstrated that the level of placental growth factor (PIGF), as a biomarker of ACS, was significantly higher in patients with OSA [33]. Thus, although a single marker might not be sufficient as a predictive biomarker of ACS in patients with OSA, a combination of several biomarkers including SNX-16 Ab may have a predictive potential in future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [32] reported that higher circulating ESM-1, previously named endothelial cell-specific molecule-1, correlated with the presence of CAD in patients with OSA. Furthermore, several studies demonstrated that the level of placental growth factor (PIGF), as a biomarker of ACS, was significantly higher in patients with OSA [33]. Thus, although a single marker might not be sufficient as a predictive biomarker of ACS in patients with OSA, a combination of several biomarkers including SNX-16 Ab may have a predictive potential in future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for these parameters, PIGF levels were significantly higher in OSA patients compared to controls and the AHI correlated with PIGF. In addition, patients with high PIGF levels showed more diseased vessels [70]. MATSUMURA et al…”
Section: Diagnosis Of Sleep Disturbances Risk Factors Predictors Anmentioning
confidence: 97%
“…As hypoxia induces PIGF, it might be hypothesised that the presence and severity of OSA influence its plasma level. BARCELO et al [70] included 538 patients admitted for ACS; 312 were defined as OSA patients (AHI >15 events•h −1 ), while 226 served as controls. The two groups differed in age, BMI and prevalence of hypertension; all these parameters had higher values in the OSA group.…”
Section: Diagnosis Of Sleep Disturbances Risk Factors Predictors Anmentioning
confidence: 99%
“…3,4 Although OSA has been suggested as an independent risk factor for cardiovascular events, the molecular mechanisms underlying such relationship are not clear to date. 5,6 During cell death, intracellular components are leaked into the bloodstream. Therefore, a myriad of biochemical markers is currently detected and quantified in blood for the assessment of human pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…; Aina Yañez 2,3 ; Laura Fueyo 1 ; Mónica de la Peña 2,4,5 ; Javier Pierola 2 ; Alicia Sánchez-de-la-Torre 5,6 ; Olga Mediano 5,7 ; Valentín Cabriada-Nuño 8 ; María José Masdeu 9 ; Joaquin Teran-Santos 5,10 ; Joaquin Duran-Cantolla 5,11 ; Juan Fernando Masa 5,12 ; Jorge Abad 5,13 ; Manuel Sanchez-de-la-Torre 5,6 ; Ferran Barbé 5,6 ; Antònia Barceló 1,2,5…”
unclassified